PENINGKATAN MOTIVASI, PARTISIPASI, DAN HASIL BELAJAR IPS MELALUI METODE BLENDED LEARNING DENGAN APLIKASI WHATSAPP GROUP - Novianto, Victor; Sari, Apri Listina (Jurnal Sosialita, 2024)
This study aims to) increase motivation, participation and improving the learning outcomes of social studies subject matter through blended learning methods with the WhatsApp Group application for students. This type of research is Classroom Action Research with two cycles consisting of three meetings in one cycle. The subjects in this study were students of class VI SDN 1 Wirun for the academic year 2021/2022, totaling 35 students. The stages in this research include planning, action, observation, and reflection. Data collection techniques in this study used questionnaires, observations, and tests. The data analysis technique used descriptive qualitative with percentages. The results showed that: (1) the blended learning method with the WhatsApp Group application could increase the social studies learning motivation, by increasing of 58.79% to 69,53% in the first cycle, and 77.12% in the second cycle; (2) the blended learning method with the WhatsApp Group application can increase social studies learning participation, with an increase in 56.57% to 65.07% in the first cycle. I, and increased again to 75.00% in cycle II; (3) the blended learning method with the WhatsApp Group application can improve social studies learning outcomes for students, with an increase of 64.91% to 73.71% in the first cycle. I, and 82.40% in the second cycle.